Ontologi Fundamental dalam Filsafat Martin Heidegger: Analisis Konsep Dasein dan Makna Ada (Sein) - Rizal Lubis; Mardhiah Abbas; Nur Syakilah Hafni Hasibuan; Lukman Hakim Gt (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This paper examines Martin Heidegger’s philosophical thought, focusing on fundamental ontology as an effort to revive the question of the meaning of Being (Sein), which has been neglected in the Western metaphysical tradition. Heidegger criticizes earlier philosophy for concentrating primarily on entities (beings) rather than addressing the essence of Being itself. Through a phenomenological-hermeneutic approach, Heidegger introduces the concept of Dasein as the distinctive mode of human existence characterized by reflective awareness of its own being. Dasein is understood as being-in-the-world, meaning that human existence is inseparable from its social, historical, and existential contexts. This paper discusses the existential structures of Dasein, including thrownness, facticity, care, temporality, and the distinction between authentic and inauthentic modes of existence. By emphasizing lived experience, Heidegger’s philosophy offers a profound and dynamic understanding of human existence beyond abstract metaphysical speculation. The paper concludes that Heidegger’s thought remains highly relevant for contemporary society, particularly in encouraging individuals to reflect on self-identity, freedom, and existential responsibility amid the complexities of modern life.